(untitled) (Clinics, 2023)
Objective: To explore whether the effect of β-catenin on MI and MI-induced cardiomyocyte apoptosis is YAP-dependent. Methods: The authors established an MI rat model by ligating the anterior descending branch of the left coronary artery, and an MI cell model by treating cardiomyocytes with H2O2. Results: β-catenin downregulation was observed in MI cardiac tissues and in H2O2-treated cardiomyocytes. Lentiviral-CTNNB1 was administered to MI rats to upregulate β-catenin expression in MI cardiac tissue. β-catenin recovery reduced the myocardial infarct area, fibrosis, and apoptotic cell death in MI rats. H2O2 treatment attenuated cell viability and induced cell death in cardiomyocytes, whereas β-catenin overexpression partially reversed these changes. Moreover, H2O2 treatment caused the deactivation of Yes-Associated Protein (YAP), as detected by increased YAP phosphorylation and reduced the nuclear localization of YAP. Upregulation of β-catenin expression reactivated YAP in H2O2-treated cardiomyocytes. Reactivation of YAP was achieved by administration of Mitochonic Acid-5 (MA-5) to H2O2-treated cardiomyocytes, and deactivation of YAP by CIL56 treatment in β-catenin-overexpressing H2O2-treated cardiomyocytes. MA-5 administration increased cell viability and repressed apoptosis in H2O2-treated cardiomyocytes, whereas CIL56 treatment counteracted the effects of β-catenin overexpression on cell survival and apoptosis. Conclusions: The present data indicate that β-catenin and YAP are effective treatment targets for MI, blocking the apoptotic death of cardiomyocytes.